2023
DOI: 10.1039/d3dt02405a
|View full text |Cite
|
Sign up to set email alerts
|

Metal-ion doping in metal–organic-frameworks: modulating the electronic structure and local coordination for enhanced oxygen evolution reaction activity

Nabeen K. Shrestha,
Supriya A. Patil,
Amol S. Salunke
et al.

Abstract: The doping of metal–organic frameworks (MOFs) with metal-ions has emerged as a powerful strategy for enhancing their catalytic performance. Doping allows for the tailoring of the electronic structure and local...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…This interaction can enable efficient charge transfer at the core branched interface, leading to faster charge and ion transfer in electrochemical reactions. 41 This suggests that there is significant electron transfer between the Fe MOF and CoNi-LDH in CoNi-LDH/Fe MOF/NF and a change in the electron structure of the elements, thus altering the charge density around the metal atoms. Such changes are expected to enhance the adsorption/desorption of oxygen, facilitating the catalytic performance for OER and ultimately improving the overall catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This interaction can enable efficient charge transfer at the core branched interface, leading to faster charge and ion transfer in electrochemical reactions. 41 This suggests that there is significant electron transfer between the Fe MOF and CoNi-LDH in CoNi-LDH/Fe MOF/NF and a change in the electron structure of the elements, thus altering the charge density around the metal atoms. Such changes are expected to enhance the adsorption/desorption of oxygen, facilitating the catalytic performance for OER and ultimately improving the overall catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…By the shift of the binding energy, it can be concluded that there is an electronic interaction between the CoNi-LDH and the Fe MOF. This interaction can enable efficient charge transfer at the core branched interface, leading to faster charge and ion transfer in electrochemical reactions . This suggests that there is significant electron transfer between the Fe MOF and CoNi-LDH in CoNi-LDH/Fe MOF/NF and a change in the electron structure of the elements, thus altering the charge density around the metal atoms.…”
Section: Resultsmentioning
confidence: 99%
“…The red shift in the Ni, C, N peak binding energies may be caused by the interaction of S 2− with the Ni sites. 61 The charge transfer ability from some electron coupling enhancement after recombination can be determined by the reduced charge transfer resistance from the Nyquist diagram obtained from electrochemical impedance spectroscopy (EIS) 62…”
Section: Resultsmentioning
confidence: 99%
“…This interaction facilitates efficient charge transfer at heterogeneous interfaces, thereby enabling faster charge and ion transfer in electrocatalytic reactions. 31,32 The above analyses suggest that significant electron transfer occurs between the Fe MOF and NiCo 2 O 4 in NiCo 2 O 4 @MOF-53(Fe), leading to alterations in the electronic structure of the elements and, subsequently, changes in the charge density around the metal atoms. These alterations, coupled with the synergistic effects at heterogeneous interfaces, hold promise for enhancing oxygen adsorption/desorption and ultimately elevating the overall catalytic activity of the OER.…”
Section: ■ Introductionmentioning
confidence: 97%